Academic Tutors/Advisors and Students Working in Partnership: Negotiating and Co-creating in “The Third Space” - McIntosh, Emily; Steele, George; Grey, David (Frontiers in Education, 2020)
In this perspectives piece we argue that technology can be used to create and facilitate “Third Space” advising, via a model of “flipped advising” which focusses on the development of quality staff-student partnerships. “Third Space” advising, using technology, encourages students and staff to work together to create and validate knowledge, connect experiences and improve the learning culture of the organisation. It also aligns with Hockings' (2010) definition of inclusive practice in learning and teaching. Whilst so much focus has been on the development of the advisor, the concept of Students as Partners (SaP) and “The Third Space” offer important lenses within which to shift the focus of advising practice away from the development of advisors and towards the development of staff-student partnerships, with a view to improving the impact and outcomes on students themselves.